2011
DOI: 10.1364/oe.19.018965
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex spectral surface plasmon resonance imaging (SPRI) sensor based on the polarization control scheme

Abstract: A two-dimensional (2D) spectral SPR sensor based on a polarization control scheme is reported in this paper. The polarization control configuration converts the phase difference between p- and s- polarization occurring at surface plasmon resonance (SPR) into corresponding color responses in spectral SPR images. A sensor resolution of 2.7 x 10(-6) RIU has been demonstrated, which corresponds to more than one order of magnitude resolution improvement (26 times) comparing to existing 2D spectral SPR sensors. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Further enhancement for commercial purposes would require careful selection of the prism material, the metal, and the CSTF material, as theoretical studies have already shown for single-SPP-wave platforms27. Moreover, the use of a lensing system after the laser-diode module would allow simultaneous measurements for a range of angles θ , and the replacement of the photodetector by an array of charge-coupled device (CCD) sensors would speed up the measurement process28.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further enhancement for commercial purposes would require careful selection of the prism material, the metal, and the CSTF material, as theoretical studies have already shown for single-SPP-wave platforms27. Moreover, the use of a lensing system after the laser-diode module would allow simultaneous measurements for a range of angles θ , and the replacement of the photodetector by an array of charge-coupled device (CCD) sensors would speed up the measurement process28.…”
Section: Resultsmentioning
confidence: 99%
“…With only one SPP-wave mode launched at a specific frequency, the multi-frequency data is optically manipulated to measure n infil correct to five decimal digits28. Incorporation of the multiple-SPP-wave platform is expected to enhance the capabilities of imaging SPP-wave sensors as well.…”
Section: Discussionmentioning
confidence: 99%
“…The excitation and probe beam radii were measured at different positions z with a beam profile camera (Ophir, Beamstar-FX-50), and used to calculate the confocal distance Z C ¼ px 2 0p =k p , m and V. The TM intensity measured at the photodetector is connected with the theory by Eq. (6). The data regression analysis gives the parameters h and D. More details could be obtained from Refs.…”
Section: Thermal Mirrormentioning
confidence: 99%
“…The methods employ coherent or incoherent light sources to heat up a material. From changes in the thermal state of the absorbing sample or its adjacent fluid, several effects can be monitored individually by measuring infrared emission, temperature change, acoustic waves, refractive index change, and surface displacement [2][3][4][5][6][7][8][9][10][11][12]. A laser-induced surface displacement, for instance, can be analyzed by probing the time-dependent intensity of a laser reflected off of the surface using the thermal mirror (TM) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional surface plasmon resonance (2D-SPR) biosensing, sharing the same principle of SPR, has been extensively used in the last 10 years to study bimolecular interactions [2][3][4][5]. The main reason behind this growth is that 2D-SPR imaging provides the advantages of real time, label free, and high throughput for rapid, sensitive detection of target biological binding reactions such as antibody-antigen or protein-DNA interactions.…”
Section: Introductionmentioning
confidence: 99%